Chest X‐ray lung imaging features in pediatric COVID‐19 and comparison with viral lower respiratory infections in young children. Issue 12 (15th September 2021) - Nino, Gustavo; Molto, Jose; Aguilar, Hector; Zember, Jonathan; Sanchez‐Jacob, Ramon; Diez, Carlos T.; Tabrizi, Pooneh R.; Mohammed, Bilal; Weinstock, Jered; Xuchen, Xilei; Kahanowitch, Ryan; Arroyo, Maria; et al.
Abstract: Rationale: Chest radiography (CXR) is a noninvasive imaging approach commonly used to evaluate lower respiratory tract infections (LRTIs) in children. However, the specific imaging patterns of pediatric coronavirus disease 2019 (COVID‐19) on CXR, their relationship to clinical outcomes, and the possible differences from LRTIs caused by other viruses in children remain to be defined. Methods: This is a cross‐sectional study of patients seen at a pediatric hospital with polymerase chain reaction (PCR)‐confirmed severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) ( n  = 95). Patients were subdivided in infants (0–2 years, n  = 27), children (3–10 years, n  = 27), and adolescents (11–19 years, n  = 41). A sample of young children (0–2 years, n  = 68) with other viral lower respiratory infections (LRTI) was included to compare their CXR features with the subset of infants (0–2 years) with COVID‐19. Results: Forty‐five percent of pediatric patients with COVID‐19 were hospitalized and 20% required admission to intensive care unit (ICU). The most common abnormalities identified were ground‐glass opacifications (GGO)/consolidations (35%) and increased peribronchial markings/cuffing (33%). GGO/consolidations were more common in older individuals and perihilar markings were more common in younger subjects. Subjects requiring hospitalization or ICU admission had significantly more GGO/consolidations in CXR ( p  < .05). Typical CXR features of pediatric viral LRTI (e.g., hyperinflation) were more common in non‐COVID‐19 viral LRTI cases than in COVID‐19 cases ( p  < .05). Conclusions: CXR may be a complemental exam in the evaluation of moderate or severe pediatric COVID‐19 cases. The severity of GGO/consolidations seen in CXR is predictive of clinically relevant outcomes. Hyperinflation could potentially aid clinical assessment in distinguishing COVID‐19 from other types of viral LRTI in young children.